China's African challenges - Raine, Sarah (Adelphi papers, 2009)
China's relations with African nationals have changed dramatically over the past decade. African oil now accounts for more than 30% of China's oil imports, and China is Africa's second-largest single-country trading partner, as well as a leading lender and infrastructure investor on the continent. Yet these developments are bringing challenges, not only for Africa and the West, but for China as well. This book examines these challenges, considering Africa as a testing ground, both for Chinese companies 'going global' and for a Chinese government that is increasingly having to deal with issues beyond its shores and immediate control. What does China need to do to protect and develop its African engagements, concerns from Western actors in Africa, and the rival presence of other emerging actors? How sustainable is the momentum that China has established in its African ventures? China's adaptations to the challenges it is facing in Africa are examined and assessed, as are the implications of these changes for China, Africa and the West. China's African engagements are certainly changing Africa, but could they also be changing China?